2022
DOI: 10.3389/fnins.2022.945796
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for randomized controlled trial to evaluate the safety and feasibility of a novel helmet to deliver transcranial light emitting diodes photobiomodulation therapy to patients with Parkinson’s disease

Abstract: IntroductionParkinson’s disease (PD) is the second most common, progressive, and debilitating neurodegenerative disease associated with aging and the most common movement disorder. Photobiomodulation (PBM), the use of non-thermal light for therapeutic purposes using laser or light emitting diodes (LED) is an emerging non-invasive treatment for a diverse range of neurological conditions. The main objectives of this clinical trial are to investigate the feasibility, safety, tolerability, and efficacy of a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Repeated neurophysiological testing (6 tests over 4 weeks) with MoCA, DSST, and trail-making tests could conceivably improve performance as a result of gaining familiarity with the test and practice; however, no papers have been published for a learning effect on these tests. Such an effect is less likely with qEEG parameters, as there is no evidence that processing speeds or power can be influenced by repeated practice, and placebo effects are less likely to persist over a full course of treatment [74,111]. In addition, further examination of current data is planned to determine if biomarkers provided by qEEG can be used to predict, early in the clinical treatment course, which patients would most likely benefit from PBM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated neurophysiological testing (6 tests over 4 weeks) with MoCA, DSST, and trail-making tests could conceivably improve performance as a result of gaining familiarity with the test and practice; however, no papers have been published for a learning effect on these tests. Such an effect is less likely with qEEG parameters, as there is no evidence that processing speeds or power can be influenced by repeated practice, and placebo effects are less likely to persist over a full course of treatment [74,111]. In addition, further examination of current data is planned to determine if biomarkers provided by qEEG can be used to predict, early in the clinical treatment course, which patients would most likely benefit from PBM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant was re-assessed by the same assessor. The protocol used in this study has been described previously [19]. Briefly, the study was a triple-blind [20], randomized placebo-controlled trial (RCT), conducted over 24 weeks entirely remotely, with online, rather than in person face-to-face contact with trial participants.…”
Section: Methodsmentioning
confidence: 99%
“…The sham device was identical but delivered no therapeutic light. The sham group was told that light was infrared and could not be seen [19]. The tPBM protocol consisted of 12 weeks of 24-min sessions, six times per week.…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators have observed similar neuroprotective effects in PD models using other species, such as rats (Oueslati et al, 2015) and flies (Vos et al, 2013), as reviewed elsewhere (Johnstone et al, 2021; Petrucco et al, 2020). In addition, clinical trials assessing the safety profile of transcranial or multi‐site PBM have established that, when applied within the correct dose window, the treatment is safe and not associated with an increase in adverse events (Blivet et al, 2022; Cassano et al, 2022; McGee et al, 2022). Histological observations in non‐human primates receiving intracranial PBM provide further evidence that PBM has an acceptable safety profile (Darlot et al, 2016; Moro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%